Health and Medication Information Resources on the World Wide Web. (April 2013) - Grossman, Sara; Zerilli, Tina
Health care practitioners have increasingly used the Internet to obtain health and medication information. The vast number of Internet Web sites providing such information and concerns with their reliability makes it essential for users to carefully select and evaluate Web sites prior to use. To this end, this article reviews the general principles to consider in this process. Moreover, as cost may limit access to subscription-based health and medication information resources with established reputability, freely accessible online resources that may serve as an invaluable addition to one's reference collection are highlighted. These include government- and organization-sponsored resources (eg, US Food and Drug Administration Web site and the American Society of Health-System Pharmacists' Drug Shortage Resource Center Web site, respectively) as well as commercial Web sites (eg, Medscape, Google Scholar). Familiarity with such online resources can assist health care professionals in their ability to efficiently navigate the Web and may potentially expedite the information gathering and decision-making process, thereby improving patient care.